2005
DOI: 10.1021/jf050463u
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Cytotoxicity, and DNA Information of Glossogyne tenuifolia

Abstract: This study investigates the antioxidant activity and cytotoxicity of Glossogyne tenuifolia extract on various cancer cell lines. The 5.8s DNA of G. tenuifolia was isolated, and the species of this plant was confirmed by NCBI's DNA database. G. tenuifolia was then extracted with ethanol and separated into several fractions using the partition procedure with water, n-butanol, and ethyl acetate (EA). Among these, the EA fraction most significantly affected the activity of DPPH(*) and superoxide anion scavenging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 35 publications
(51 reference statements)
4
50
0
Order By: Relevance
“…The results indicated that algal extracts had no significant cytotoxic activity against Hep 3B cells in all treated concentrations (5-50 lg/mL). Previous studies indicated that the antioxidant activities may have synergistic effects on anticancer activity, proliferation inhibition, and apoptosis of human tumor or cancer cell lines (Seeram et al 2004;Shao et al 2004;Hsu et al 2005). In our study, the result of cytotoxicity has shown correlation between the results of antioxidant and cytotoxic activity since there was no cytotoxicity on Hep 3B cells with moderate antioxidant activity of the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that algal extracts had no significant cytotoxic activity against Hep 3B cells in all treated concentrations (5-50 lg/mL). Previous studies indicated that the antioxidant activities may have synergistic effects on anticancer activity, proliferation inhibition, and apoptosis of human tumor or cancer cell lines (Seeram et al 2004;Shao et al 2004;Hsu et al 2005). In our study, the result of cytotoxicity has shown correlation between the results of antioxidant and cytotoxic activity since there was no cytotoxicity on Hep 3B cells with moderate antioxidant activity of the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic effect (Co-activity) play a vital role during the estimation of antioxidant activity of plant extracts as a complex mixture containing a large number of combined compounds. These compounds may be reinforcing each other leading to raising their antioxidant potential and vice versa [20,29,30].…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…Some effective components from GT have been isolated and shown to exert combinatorial anti-inflammatory and antiviral effects in production of some mediators, i.e., TNF-alpha, IL-6 and IFN-gamma in activated human whole blood [10]. Its components, e.g., luteolin and luteolin-7-glucoside, play a crucial role in increasing scavenging capacity of free radicals and inhibiting the growth of hepatoma cancer cell lines [11].…”
Section: Introductionmentioning
confidence: 99%